2022
DOI: 10.3126/jaar.v9i1.44052
|View full text |Cite
|
Sign up to set email alerts
|

Compliance on Diet and Exercise among Diabetic Patient in Referral Hospital of Morang District

Abstract: Diabetes is a serious health problem that threatens the quality of life of with diabetes, the success of long term maintenance therapy for diabetes depends largely on the patient compliance with diet and exercise. Thus, this study aim to assess the compliance on Diet and Exercise among diabetic patient in a Referral Hospital of Morang District. Methodology: A cross sectional descriptive study was conducted among type 2 diabetic patient in medical OPD of Koshi Hospital   through face to face interview Data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…A study done by Bonger and Tariku (2018), revealed that the extent to which individuals adhere to the recommended management of T2DM is substantially low whereby about 80% of diabetes patients did not adhere to the recommended diet management and self-monitoring of blood glucose level, while a majority (96%) of the respondents adhere to the prescribed medications. A study done by Rijal et al (2022), to assess compliance of diabetes patients to diet and exercise revealed that compliance on diet was reasonable compared to exercise aspects. Several studies indicated that demographic and socioeconomic, clinical, and healthrelated characteristics such as age, religion, employment status, sex, family support, duration of T2DM, presence of comorbidities and diabetes-related complications influence compliance to recommended management practices (Ayele et al, 2018;Zarei et al, 2022;Zewdie et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…A study done by Bonger and Tariku (2018), revealed that the extent to which individuals adhere to the recommended management of T2DM is substantially low whereby about 80% of diabetes patients did not adhere to the recommended diet management and self-monitoring of blood glucose level, while a majority (96%) of the respondents adhere to the prescribed medications. A study done by Rijal et al (2022), to assess compliance of diabetes patients to diet and exercise revealed that compliance on diet was reasonable compared to exercise aspects. Several studies indicated that demographic and socioeconomic, clinical, and healthrelated characteristics such as age, religion, employment status, sex, family support, duration of T2DM, presence of comorbidities and diabetes-related complications influence compliance to recommended management practices (Ayele et al, 2018;Zarei et al, 2022;Zewdie et al, 2022).…”
Section: Introductionmentioning
confidence: 99%